Hematological parameters in rats poisoned with cadmium nitrate and in biocorrection with the infusion of Beta vulgarisseeds - Konkabayeva А.Е.; Erubay А.S.; Gaibel Е. (Fundamental and Experimental Biology, 2020)
Nowadays, using plant extracts and infusions as protectors against the impact of heavy metals, the molecular mechanisms, protective and adaptive reactions of plants are studied. The purpose of this article was to study the protective properties of beetroot seeds infusion in acute and sub-acute poisoning of rats with cadmium nitrate. For this experiment, we used 50 male rats. The animals were exposed to Cd nitrate, with an initial weight of 180 ± 30 g. The first groups of rats were injected with cadmium nitrate at a dose of 0.1 g/L intraperitoneally, the second groups received a 0.01 % solution of cadmium nitrate, 1 mL, 5 days a week, orally for 10 and 24 days. General blood tests and biochemical parameters in rats were investigated. By biochemical parameters, we determined liver enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), bilirubin, glucose, urea, creatinine, and total protein. The mean ± SEM values were calculated for each group to determine the significance of the intergroup difference. Each parameter was analyzed separate-ly using the one-way analysis of variance (ANOVA) test. To determine the difference between groups, Stu-dent’s «t»-test was used. Studies showed the presence of variations in the parameters of leukocytes, erythrocytes and platelets depending on the period of days of poisoning and biocorrection. There were small changes in the content of urea, creatinine, and protein, which were not reliably confirmed. As a result, our research al-lowed asserting that the use of Beta vulgarisinfusion in acute and subacute experiments with poisoning of animals with cadmium nitrate had a positive hepatoprotective effect.